The impact of paternal age on cumulative assisted reproductive technology outcomes - Farabet, Clemence; Pirtea, Paul; Benammar, Achraf; De Ziegler, Dominique; Marchiori, Claire; Vallée, Alexandre; Ayoubi, Jean-Marc (Frontiers in Medicine, 2024)
Objective To investigate the impact of paternal age on cumulative live birth rate in ART. Design Retrospective single-center cohort study. Patient(s) All female patients aged 18–43 years and male patients aged 18–60 years, who performed their first ART cycle between January 2018 and December 2020, were included. Main outcome measure(s) The primary outcome, cumulative live birth rate (cLBR), was estimated following fresh or frozen embryo transfers issued from an ART cycle. Secondary outcomes included the cumulative pregnancy rate (cPR) and miscarriage rate. Subgroup analyzes were performed as follows: men <45 and ≥ 45; female <35, 35–38, and > 38 years. Result(s) A total of 2,358 couples were included in this study. The sperm quantity of male patients within both age groups was divided in two groups: normal and abnormal, which were found to be in significantly equal proportions. There were significantly fewer current smokers in the male group ≥45. The cPR was 0.5301 in the group <45 and 0.3111 in the group ≥45, with a p-value <0.001. Analysis according to the female age revealed that, in the female group >38, the cLBR rate was 0.26 for men <45 and 0.19 for men ≥45, with a p-value of 0.061. Additionally, the cPR was 0.34 in the male group <45 and 0.21 in the group ≥45, with a p-value <0.001. In the female group between 35 and 38 years of age, the cLBR was 0.44 in the male group <45 and 0.3 in the male group ≥45, with a p-value of 0.031. The cPR was 0.49 in the male group <45 and 0.34 in the group ≥45, p = 0.036. Within the female group <35, we observed non-significant results. The miscarriage rate results were not significantly different for women ≤38. Conclusion According to the results from our study, male age ≥ 45 has a significant impact on cumulative ART outcomes.